Menakar Kontribusi Materiil Hukum Pidana Islam Terhadap KUHP Baru Indonesia; Kajian Aspek Tindak Pidana - Zubaeri, Ahmad; Abdillah, Junaidi; Maksun, Maksun (Direktorat Jenderal Peraturan Perundang-undang, Kementerian Hukum, 2025)
The new Indonesian Penal Code (KUHP), introduced through Law No. 1 of 2023, represents a transformation of the national criminal law by dialectically adopting elements of Islamic Criminal Law (HPI). These reforms encompass sentencing, penal systems, and sanctions while emphasizing religious values, modern legal needs, and social harmony. This study employs a documentary-historical method to analyze the dialectics between Islamic law and the new KUHP, identifying five key elements: the principle of legality, unwritten law, criteria for unwritten law, retroactive principles, and the classification of criminal offenses.The analysis reveals that HPI significantly contributes to the new KUHP through concepts such as restorative justice, the principle of jalb al-mashalih wa dar’u al-mafasid (promoting benefits and preventing harm), and flexibility in the form of takzir. While the new KUHP successfully reflects values of democratization, recodification, and harmonization, certain HPI elements, such as the scope of unwritten law based on maqashid al-syari'ah and the application of retroactive principles for crimes with broad societal impact, are not fully accommodated. This study underscores the importance of synergy between Indonesian cultural values and religious law to create a functional, just, and sustainable criminal justice system.